EFFECT OF CADMIUM COATING ON THE FATIGUE STRENGTH OF AISI 4140 STEEL USED IN OIL AND GAS COMPANY - Santos, Jefferson R. M. [UNESP]; Voorwald, Herman J. C. [UNESP]; Gomes, JFS; Meguid, S. A. (Inegi-feup, 2017)
The influence of electrodeposited coating of cadmium on AISI 4140 steel has been studied at room temperature in axial fatigue. Axial fatigue testing was performed using studs at base metal and cadmium coated conditions. Oscillating stresses with maximum stresses (sigma(max)) up to 780 MPa, stress ratio R=0.1 and frequency 20 Hz have been applied. For a given sigma(max), the lifetime decrease for threaded samples and even more when cadmium coating is applied. The reason is explained by a stress concentration induced at the thread, shown herein by Finite Element Method, be intensified by crack propagation at electrodeposited cadmium. Scanning Electron Microscope was used to show the fracture surfaces for both cadmium coated and base metal studs where is possible to identify many cracks at the coated surface.
Keywords: fatigue; AISI 4140 steel; cadmium coating; oil and gas